Habiting at the seventh and jiménez street in bogotá. corporeity, history and place (2007)
The document analyzes the habitat as a result from the interaction between the body and place in scopes of the corporality. The construction of the carpet approaches that constitutes living in a significant space of Bogotá, the crossing of the Jiménez Avenue with Carrera Séptima in the diverse historical periods from the birth of the city until now, integrating memory and the quotidianity like inherent aspects of the experiences of the place. It is as well the study assumes the body from its entailment with the environment, in terms of perception, where from the senses it takes shape the experience and the appropriation forming the meaning of the place. One second instance constitutes the corporeity and thus the projection towards the Other, in the public space, the street, contemplates “alteridad” and “proxemia” like edges of sociology that hit the study of the daily practices of living. Historical sources have been taken boarded, of narration, chronicle and literature in urban novel and new historical novel like support resource that allows to delineate in a vivid way the experience of living at every raised historical moment. The habitat thus constitutes the plot that, with the support of the resulting physical spaces of socio-cultural processes, forms the physical territories as much as symbolic and ideal which define and characterize the place.